Effects of bread with Nigella sativa on hematologic factors in metabolic syndrome patients - Mohtashami, Alireza; Mahaki, Behzad; Azadbakht, Leila; Entezari, Mohammad Hassan (Progress in Nutrition, 2018)
Background: Nigella sativa (N. sativa) has been used in traditional medicine and many studies have been performed in different communities in order to reveal the effects of it on medical disorders and chronic diseases. Purpose: The aim of this study was the investigation of effects of bread with N. sativa on hematologic factors in metabolic syndrome (MetS) patients. Material and methods: A randomized, double-blind, cross-over, clinical trial was conducted in 51 MetS patients of both sexes with age group of 20-65 years old in Chalus, north of Iran. Patients randomly divided in two groups. In phase 1, Intervention group (A, n =27) received daily a regular bread with N. sativa and wheat bran and control group (B, n=24) received the same bread without N. sativa for 2 month. After 2 weeks wash out period, phase 2 was started with replacement of two groups. Measuring of red blood cells (RBC), white blood cells (WBC), prothrombin time(Pt), hematocrite (Hct) and hemoglobin (Hb) was performed for patients in before and after of two phases. Results: In this study evaluated treatment, sequence and time effects of crossover intervention and revealed that consumption of bread with N. sativa has not significant treatment and sequence effects on RBC, WBC, PT, Hct and Hb (p>0.05). Time effect was only significant on RBC (P0.05). Conclusion: Consumption of bread with N. sativa has not significant effect on hematologic factors in MetS patients.